뇌파 훈련을 시행한 주의력결핍 과잉행동장애 아동의 증례 보고 - 정명숙; Myong Suk Jung; 강희철; Hee Chul Kang; 이승기; Seung Gi Lee (동의신경정신과학회지, 2008)
Attention Deficif and Hyperactivity Disorder(ADHD) is a behavioral disoerder characterized by inattentiveness, impulsivity and hyperactivity. This is the case of a ADHD child treated with Neurofeedback therapy. ADHD Diagnotic System(ADS), Conner;s parent rating scale, ADHD-Rating Scale(ARS), Korean Child Behavior Checklist(K-CBCL) were compared between before and after Neurofeedback theraphy. And the EEG(Theta wave, SMR wave and Beta wave) data of each ession was analysed. As a result, Neurofeedback therapy is efficient in the treatment of ADHD.